A model of cooperation platform for entities involved in the agricultural market open to innovations in Poland - Zenon Pokojski (Economic and Environmental Studies (E&ES), 2018)
There are few publications on the subject of business models open to innovations in Poland, especially relating to cases of their practical application. The article analyses various types of open innovations and the possibility of using them in the conditions of the Polish agricultural market. After reviewing the literature, analysing cases of chemical companies, conducting interviews with members of the Grupa Azoty Pulawy consortium, the author proposes a model of cooperation platform for entities from various sectors that systemically combines open inbound and outbound innovations with the requirements of the business model.
Keywords: O32; O31; 330; open innovation; cooperation model; business model; commercialization of innovations